Insularité et dépeuplement : le cas de l’île de Flores aux Açores (Portugal) - Louis Marrou (Espace populations sociétés, 2016)
The island of Flores in the Azores archipelago has been inhabited for over 500 years. However, for more than 50 years now, this Portuguese territory has experienced continuous depopulation. It has lost more than half of its population, and its density is now less than 30 inhabitants/km.2 This paper attempts to spatialize these phenomena and understand the depopulation factors at play. (These include mobility, isolation, and spatial competition.) This has become extremely urgent because regional, national and European bonds that have contributed to the sustainability of the territory are now under threat.